Kepemimpinan Kepala Ruangan dan Kepuasan Kerja Perawat Pelaksana - Yulia, Revi; Wahyuni, Fatma Sri; Lubis, Mutia Amalia (Universitas Fort De Kock Bukittinggi, 2020)
Background: Job satisfaction is a subjective state based on a comparison of what is actually received by a person from his job compared to what is expected. The study aims to see description of job satisfaction of nurses and to see the relationship between the leadership of the head of the room with the work satisfaction of the implementing nurses in the inpatient room of Batam Hospital. Method: This type of research is analytic descriptive with cross sectional approach. Samples are all nurses in the inpatient room RSBK with a sample of 88 people, with sampling techniques, total sampling. Results: The results of the bivariate chi-square statistical test showed the results of a significant relationship between leadership and the work satisfaction of implementing nurses. Conclusion: Nursing management is expected to always control and conduct training related to nursing leadership (leadership training for the head of the room)